Circadian Profiling of the Arabidopsis Proteome Using 2D-DIGE - Choudhary, Mani K.; Nomura, Yuko; Shi, Hua; Nakagami, Hirofumi; Somers, David E. (Frontiers in Plant Science, 2016)
Clock-generated biological rhythms provide an adaptive advantage to an organism, result in increased fitness and survival. To better elucidate the plant response to the circadian system, we surveyed protein oscillations in Arabidopsis seedlings under constant light. Using large-scale two-dimensional difference in gel electrophoresis (2D-DIGE) the abundance of more than one thousand proteins spots was reproducibly resolved quantified and profiled across a circadian time series. A comparison between phenol-extracted samples and RuBisCO-depleted extracts identified 71 and 40 rhythmically-expressed proteins, respectively, and between 30-40% of these derive from non-rhythmic transcripts. These included proteins influencing transcriptional regulation, translation, metabolism, photosynthesis, protein chaperones and stress-mediated responses. The phasing of maximum expression for the cyclic proteins was similar for both datasets, with a nearly even distribution of peak phases across the time series. STRING clustering analysis identified two interaction networks with a notable number of oscillating proteins: plastid-based and cytosolic chaperones and ten proteins involved in photosynthesis. The oscillation of the ABA receptor, PYR1/RCAR11, with peak expression near dusk adds to a growing body of evidence that intimately ties ABA signaling to the circadian system. Taken together, this study provides new insights into the importance of post-transcriptional circadian control of plant physiology and metabolism.